Effect of Rivaroxaban and Aspirin in Patients With Peripheral Artery Disease Undergoing Surgical Revascularization: Insights From the VOYAGER PAD Trial. Issue 14 (12th August 2021) - Debus, E. Sebastian; Nehler, Mark R.; Govsyeyev, Nicholas; Bauersachs, Rupert M.; Anand, Sonia S.; Patel, Manesh R.; Fanelli, Fabrizio; Capell, Warren H.; Brackin, Taylor; Hinterreiter, Franz; Krievins, Dainis; Nault, Patrice; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Patients with peripheral artery disease requiring lower extremity revascularization (LER) are at high risk of adverse limb and cardiovascular events. The VOYAGER PAD trial (Vascular Outcomes Study of ASA [Acetylsalicylic Acid] Along With Rivaroxaban in Endovascular or Surgical Limb Revascularization for PAD) demonstrated that rivaroxaban significantly reduced this risk. The efficacy and safety of rivaroxaban has not been described in patients who underwent surgical LER. Methods: The VOYAGER PAD trial randomized patients with peripheral artery disease after surgical and endovascular LER to rivaroxaban 2.5 mg twice daily plus aspirin or matching placebo plus aspirin and followed for a median of 28 months. The primary end point was a composite of acute limb ischemia, major vascular amputation, myocardial infarction, ischemic stroke, or cardiovascular death. The principal safety outcome was Thrombolysis in Myocardial Infarction major bleeding. International Society on Thrombosis and Haemostasis bleeding was a secondary safety outcome. All efficacy and safety outcomes were adjudicated by a blinded independent committee. Results: Of the 6564 randomized, 2185 (33%) underwent surgical LER and 4379 (67%) endovascular. Compared with placebo, rivaroxaban reduced the primary end point consistently regardless of LER method ( P -interaction, 0.43). After surgical LER, the primary efficacy outcome occurred in 199 (18.4%) patients in the rivaroxaban group and 242 (22.0%) patients in the placebo group with a cumulative incidence at 3 years of 19.7% and 23.9%, respectively (hazard ratio, 0.81 [95% CI, 0.67–0.98]; P =0.026). In the overall trial, Thrombolysis in Myocardial Infarction major bleeding and International Society on Thrombosis and Haemostasis major bleeding were increased with rivaroxaban. There was no heterogeneity for Thrombolysis in Myocardial Infarction major bleeding ( P -interaction, 0.17) or International Society on Thrombosis and Haemostasis major bleeding ( P -interaction, 0.73) on the basis of the LER approach. After surgical LER, the principal safety outcome occurred in 11 (1.0%) patients in the rivaroxaban group and 13 (1.2%) patients in the placebo group; 3-year cumulative incidence was 1.3% and 1.4%, respectively (hazard ratio, 0.88 [95% CI, 0.39–1.95]; P =0.75) Among surgical patients, the composite of fatal bleeding or intracranial hemorrhage ( P =0.95) and postprocedural bleeding requiring intervention ( P =0.93) was not significantly increased. Conclusions: The efficacy of rivaroxaban is associated with a benefit in patients who underwent surgical LER. Although bleeding was increased with rivaroxaban plus aspirin, the incidence was low, with no significant increase in fatal bleeding, intracranial hemorrhage, or postprocedural bleeds requiring intervention. Registration: URL: http://www.clinicaltrials.gov ; Unique Identifier: NCT02504216.